The Effects of Sleep, Posterior Interference and Type of Exercise (Physical and Combine it With Observation of Action) on Consolidate Processing Consolidate Beginner Children's Motor Memory in Volleyball - Soheila Rajaee; Parvaneh ShamsipourDehkordi; Maryam Abdoshahi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Memory consolidation is a set of processes that converts memory from an unstable state to a stable one. Various factors affect the consolidation of memory, including sleep and the type of exercise have an effect on consolidation. Given that little research on consolidation has used a motor task for the age group of children, the aim of thise study was to investigate the effect of sleep, type of exercise (Physical and Combine it whit observation of action) and posterior interference on consolidation processing based on stability and promotion of motor memory.Methods This research was a semi-experimental study with an pretest- posttest design. The statistical population included girls aged 10 to 12 years who had registered in volleyball in clubs in east Tehran in 2018. The sample included 62 novice girls in volleyball who were selected by available sampling method according to the inclusion and exclusion criteria. The experiments were divided into combined observation and physical exercise groups. The tools used in this study were, Landgrafe and Abetz child health questionnaire (1996), owens children's sleep habits questionnaire (2000), Aahperd Volleyball Serving Test (1969). Data were analyzed using combined factor analysis of variance with repeated measures and Benfferroni post hoc test.Results The results of the analysis of variance-covariance with repeated measures showed that a night's sleep has a positive effect on stabilizing processing based on stability and promoting motor memory in children (F=15.40, P=0.001), but the type of exercise (F=0.18, P=0.67), (Physically or observational) and type of posterior interference (performing or observing the action) (F=0.48, P=0.489) have no significant effect on consolidation processing. Comparison of averages showed that physical practice is more stable and promotion motor memory than observation.Conclusion Coaches and educators are recommended in addition to physical exercise, children can use observational exercise to process memory consolidation